A Study to Determinants of Risk Management and Prevention in Credit Card Business in Commercial Banks - GholamReza Zandi; Rezvan Torabi; Liu Han Min; Ananda Devan Sivalingam; Tan Teck Khong (Journal of Information Technology Management)
The purpose of this study is to explore and determinants the risk management and prevention in credit card business of Malaysian commercial banks. There were five factors derived through the literature and experimental investigation that are affecting the banks due to credit card which are External Fraud Risk, Internal Operational Risk, Credit Risk of Cardholders, Science and Technology and Intermediary Agency Trades Risk. Hence, 250 respondents participated in this study from state of Selangor and Federal Capital Kuala Lumpur. The data was collected and analyzed by SPPS software and it was concluded that that External fraud risk, Internal operational risk, Credit risk of Cardholder, Science and technology are positively correlated with the Credit card business risks of commercial Banks in Malaysia. These papers have highlighted suggestion for future research to develop this study further by considering the data derived from this study by using Delphi Technique